2012
DOI: 10.1007/s11524-012-9769-4
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Consequences of Terrorism on Maternal–Child Health in New York City and Madrid

Abstract: Past research provides evidence for trajectories of health and wellness among individuals following disasters that follow specific pathways of resilience, resistance, recovery, or continued dysfunction. These individual responses are influenced by event type and pre-event capacities. This study was designed to utilize the trajectories of health model to determine if it translates to population health. We identified terrorist attacks that could potentially impact population health rather than only selected indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…There were fewer direct associations with current disruption or perceptions of recovery, making them unlikely mediators. To our knowledge, only one previous study that has examined the long-term effect of disaster on pregnancy, finding mixed results on the long-term effects of the September 11 th attacks and Madrid train bombings (20). This study is generally consistent with previous research finding that disaster affects infant growth and gestational age (6), although our results were not always robust to adjustment for confounders.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There were fewer direct associations with current disruption or perceptions of recovery, making them unlikely mediators. To our knowledge, only one previous study that has examined the long-term effect of disaster on pregnancy, finding mixed results on the long-term effects of the September 11 th attacks and Madrid train bombings (20). This study is generally consistent with previous research finding that disaster affects infant growth and gestational age (6), although our results were not always robust to adjustment for confounders.…”
Section: Discussionmentioning
confidence: 94%
“…This study examined both New York after the September 11 attacks and Madrid after the train bombing, and found a long-term increase in infant mortality in New York, but no increase in low birthweight or preterm birth, and no long-term effects on low birthweight, preterm birth, or infant mortality in Madrid (20). This study relied on vital records data, and so had no information about the individual experiences of the women either during or after the attacks.…”
Section: Introductionmentioning
confidence: 97%
“…In spite of this general perception, the objective data for 2003 were three casualties, reduced to zero in 2017. It is true, however, that terrorism is a health problem in terms of injuries, which causes social and emotional damage, and that Spain has a long terrorism-related history, which easily explains its importance in this country [47,48]. Actually, there were terrorist attacks in the year 2000 (26 casualties), 2001 (15 casualties), and 2002 (5 casualties) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Current Centers for Disease Control Guidelines recommend admission of pregnant patients in the second and third trimester after exposure to blast injury, but make no other specific recommendations for their care 7. Nevertheless, reports of pregnant women injured following terrorist activities8 9 recognise placental abruption and UR as complications of blast injury. Awwad et al 10 reported UR requiring perimortem CS as a complication of blast injury; however, we have not found a previous report of a blast injury causing placental abruption where both mother and baby survived.…”
Section: Discussionmentioning
confidence: 99%